Pancreatic Cancer With Malignant Ascites: Clinical Features and Outcomes. Issue 3 (April 2015) - Takahara, Naminatsu; Isayama, Hiroyuki; Nakai, Yousuke; Sasaki, Takashi; Saito, Kei; Hamada, Tsuyoshi; Mizuno, Suguru; Miyabayashi, Koji; Mohri, Dai; Kogure, Hirofumi; Matsubara, Saburo; Yamamoto, Natsuyo; et al.
Abstract : Objectives: Malignant ascites (MA) caused by peritoneal carcinomatosis is not uncommon in patients with pancreatic cancer. However, the clinical features and outcomes in these patients remain to be elucidated. Methods: Baseline characteristics and overall survival (OS) of consecutive patients with advanced pancreatic cancer who presented with MA were retrospectively evaluated. Results: Of 494 patients with advanced pancreatic cancer, 73 (15%) presented with MA. Patients with synchronous MA (n = 21), compared with those with metachronous MA (n = 52), had better performance status ( P = 0.02), smaller amount of ascites ( P < 0.01), and higher chance of receiving chemotherapy (57% vs 17%, P < 0.01), and resulted in longer OS (115 vs 42 days, P < 0.01). Overall survival was significantly longer in patients receiving chemotherapy than in those with best supportive care alone (124 vs 50 days, P < 0.01). In a multivariate analysis, chemotherapy was prognostic in addition to performance status, CRP, and small amount of MA; the hazard ratio of chemotherapy was 0.46, compared with best supportive care alone ( P = 0.02). Conclusions: Although the prognosis of pancreatic cancer patients with MA remains poor, selected patients may be candidate for chemotherapy, regardless of the timing of appearance of MA.